The effect of voice emotion response on brand recall by gender - Wang, W.; Pestana, M.H.; Moutinho, L. (The Routledge companion to marketing research, 2021)
This research collaborates with researchers in the field of human-computer interaction and suggests an alternative method: the voice emotion response in Mandarin Chinese and analyse the effect of voice emotion responses on brand recall by gender in Taiwan. The bibliographic revision was submitted to a scientometric analysis through CiteSpace. Voice emotion software and an audio-recording equipment were conducted in a laboratory and field environment and the results were analysed through Optimal Data Analysis. Brand recall in Mandarin speech is positively associated with emotions and vary by products according to gender. Men have better recall scores when related to cars, whereas women scored higher when dealing with soft drinks and fast-food. This paper provides opportunities for companies to improve customer relationships. Marketers involved with advertising have this body of knowledge to capture consumers’emotions toward their products and services on which to base their marketing intelligence gathering and strategic planning.